THE IMPORTANCE OF ARAB COUNTRIES IN THE RELATIONS OF THE WORLD TOURISM ECONOMY IN THE LATE 20TH AND EARLY 21ST CENTURIES (International journal of artificial intelligence, 2024)
This article examines the growing importance of Arab countries in the global tourism economy from the late 20th century to the early 21st century. It analyzes the main factors of the development of tourism in this region, including economic diversification, cultural heritage and natural attractions. The study also addresses issues such as political instability and sustainability issues in the development of tourism in these countries. A combination of qualitative and quantitative methods was used to assess the impact of tourism on economic growth, cultural preservation and international relations. The results highlight the emerging role of Arab countries in global tourism dynamics and offer political proposals to ensure sustainable growth in the sector.